2016
DOI: 10.1177/0022022115626513
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Psychological Safety

Abstract: Immigration entails the risk of feeling disconnected in the receiving society, in both everyday life and the workplace. This may affect the way immigrant employees relate to their job and their workplace. In this article, we investigate the affective commitment of Turkish immigrant employees in Germany (TG) and their subsequent work engagement, mental health, and turnover intention. Specifically, we compared TG (n = 201) to both German employees in Germany (GG; n = 1,406) and Turkish employees in Turkey (TT; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Researchers (Zia and Syed, 2013;Fletcher et al, 2008) found that because workplaces are highly competitive, trusting affiliations are strenuous to have, which leads to difficulty in taking interpersonal risks if they are not well connected with other employees or members of the team. Given the rising concern, Ulusoy et al (2016) andO ¨ge et al (2018) have noted the need to study workplace loneliness and psychological safety. The work of Edmondson and Lei (2014) has not referred to workplace loneliness as an antecedent of psychological safety.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Researchers (Zia and Syed, 2013;Fletcher et al, 2008) found that because workplaces are highly competitive, trusting affiliations are strenuous to have, which leads to difficulty in taking interpersonal risks if they are not well connected with other employees or members of the team. Given the rising concern, Ulusoy et al (2016) andO ¨ge et al (2018) have noted the need to study workplace loneliness and psychological safety. The work of Edmondson and Lei (2014) has not referred to workplace loneliness as an antecedent of psychological safety.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A large number of studies investigated the effect of psychological safety on learning and found a positive relation (Edmondson, 2004;Carmeli and Gittell, 2009;Nembhard and Edmondson, 2012;Kumako and Asumeng, 2013;Ortega, et al, 2014;Roussin, MacLean and Rudolph, 2016;Frazier, et al, 2017;Kim, Lee and Connerton, 2020). Moreover, psychological safety was found to result in knowledge sharing, learning from failures, employee satisfaction, engagement, commitment, and creativity (May, Gilson and Harter, 2004;Carmeli and Gittell, 2009;Bornemisza, 2013;Ulusoy et al, 2016;Frazier et al, 2017). Besides, there are other studies identifying the role of psychological safety that weakens or strengthens other relationships (Edmondson, 2018).…”
Section: Psychological Safetymentioning
confidence: 99%
“…A previous systematic review presented possible pathways from job resources (e.g., supportive leadership behavior) through PS to positive and negative work outcomes (e.g., stress, conflict, and performance) in the integrative theoretical framework of PS 1 . Some previous studies suggested that PS reduced the risk of poor mental health outcomes such as burnout, stress, and diminished well-being, by increasing social support in HCW and non-HCW 11,12 . However, the effect of PS on mental health has not been empirically examined.…”
Section: Introductionmentioning
confidence: 99%